Penerapan User-Centered Design Method Guna Pembaruan Substansi Terhadap Informasi dan Data-Data pada Website - Vederico Pitsalitz Sabandar; Kelik Sussolaikah; Riovan Styx Roring (Journal of Computer System and Informatics (JoSYC), 2022)
The research carried out aims to carry out a substantive update of information and data on the website of the Mathematics Education Study Program, FKIP, UNPATTI. The research carried out applies the User-Centered Design (UCD) method, which is a method in a design that focuses on user needs. Broadly speaking, in using the UCD method, the research conducted was divided into three main stages, namely analysis, design, and evaluation with the process of implementing the UCD method using ISO 9241-210: 2019. Furthermore, the research conducted involved 44 respondents who were used as target users and categorized into two groups, namely the academic community (lecturers and students) and non-academic members (prospective students and alumni). Based on the results of the research conducted, 9 formulations of user requirements were obtained, followed by making a website interface design in the form of a prototype (wireframe). Furthermore, the resulting prototype is then evaluated by providing a series of task scenarios to guide users in using the website. The evaluation was carried out using a qualitative survey method, namely interview activities aimed at obtaining feedback regarding user experience on the appearance of the website design interface as well as obtaining recommendations and suggestions for further development. Based on the evaluation carried out, the result was that the resulting website design met user needs. This is because the design is produced as a solution to user needs, by a series of requirements submitted by users. In addition, the design of the website interface also provides a satisfying user experience. Therefore, the research carried out does not occur repetition (iteration), so it can proceed to the implementation stage. Furthermore, at the prototype implementation stage, the results of the website design are then converted into an interface display using the Content Management System (CMS) Framework and supporting programming languages ​​such as HTML, CSS, PHP, and Javascript. The website of the Mathematics Education Study Program which has been successfully updated for the substance of both the information and data contained therein can then be accessed via the official link of the Mathematics Education Study Program, FKIP, UNPATTI..